Nutrition, Choice and Health-Related Claims - De Magistris, Tiziana (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book presents different articles focused on the role of nutritional properties and/or health-related claims on choice preferences, choice behavior, healthy eating/healthy diet, and the willingness to pay for certain foods.